Poland's Accession to the European Union: Demand for Protection of Selected Sensitive Products - Jarko Fidrmuc; Peter Huber; Jan Jakub Michalek (Austrian Institute of Economic Research (WIFO), 1999)
This paper analyses the expected changes in external tariffs and imports in Poland after accession to the European Union. We find that around 14% of all manufacturing commodity groups in the Harmonised System will experience tariff reductions of over 10 percentage points, while for agricultural goods tariff comparisons are complicated by very different tariff systems and may be overrated since applied tariffs are often lower than those committed. Based on gravity estimates we also find that only few - relatively narrowly defined commodities - will experience import growth rates of above 20%. More widely defined sensitive commodities are subject to a much smaller but still important import growth.
Keywords: 330; Eastern Enlargement of EU; trade liberalisation; trade restrictions; adjustment costs; EU-Mitgliedschaft; Protektionismus; Polen